Analysis of the discouraged worker phenomenon. Evidence from micro data - John K. Dagsvik; Tom Kornstad; Terje Skjerpen (Statistics Norway, Research Department, 2006)
In this paper we analyze labor force participation with particular reference to the discouraged worker effect. The theoretical point of departure is a simple model where the worker evaluates the expected utility of searching for work, and decides to participate in the labor market if the expected utility of the search exceeds the utility of not working. With suitable assumptions about unobserved and observed heterogeneity we derive an empirical model for the probability that the worker will be unemployed or employed as a function of the probability of getting a job, given that the worker searches for work. The model is estimated on Norwegian micro-data consisting of independent cross sections over 15 years. The results indicate that there is a substantial discouraged worker effect.
Keywords: J21; J22; J64; 330; Discouraged workers; Labor force participation; Random utility modelling